2023
DOI: 10.1021/acs.energyfuels.2c03216
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Controlling Factors on Enhanced Gas Recovery by CO2 Injection in Shale Gas Reservoirs

Abstract: Development of shale gas reservoirs is the fastest growing area on a large scale globally due to their potential reserves. CO2 has a great affinity to be adsorbed on shale organic surface over CH4. Therefore, CO2 injection into shale reservoirs initiates a potential for enhanced gas recovery and CO2 geological sequestration. The efficiency of CO2 enhanced gas recovery (CO2-EGR) is mainly dominated by several shale properties and engineering design parameters. However, due to the heterogeneity of shale reservoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 72 publications
(176 reference statements)
0
14
0
Order By: Relevance
“…In fact, the oil recovery from fractured core samples exhibited an increase of approximately 14% compared to core samples without fractures. 48 Mansi et al 49 investigated the influence of permeability on the performance of flue gas injection. Their experimental findings highlight that flue gas injection is particularly advantageous for enhancing gas recovery (EGR) in shallow shale reservoirs characterized by high fracture permeability.…”
Section: Effect Of Fracture and Matrix Permeability During Flue Gas I...mentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, the oil recovery from fractured core samples exhibited an increase of approximately 14% compared to core samples without fractures. 48 Mansi et al 49 investigated the influence of permeability on the performance of flue gas injection. Their experimental findings highlight that flue gas injection is particularly advantageous for enhancing gas recovery (EGR) in shallow shale reservoirs characterized by high fracture permeability.…”
Section: Effect Of Fracture and Matrix Permeability During Flue Gas I...mentioning
confidence: 99%
“…50 Table 4 provides a concise summary of the effects of matrix and fracture permeability on flue gas projects. (46) experimental in reservoirs with high matrix permeabilities, crude oil migrated from macro pores to medium and fine pores, resulting in higher oil production compared to reservoirs with low matrix permeabilities (47) simulation using CMG-STARS if the matrix permeability falls below a certain threshold, the oil production rate remains unchanged even in the presence of cyclic steam-assisted flue gas injection scenarios (48) experimental fractures played a major role in facilitating crude oil migration; in fact, the oil recovery from fractured core samples exhibited an increase of approximately 14% compared to core samples without fractures (49) experimental applying hydraulic fracturing method for increasing the permeability of the rock and improving the conductivity in pore scale can increase the efficiency of flue gas injection (50) experimental under immiscible conditions, the oil recovery factor was lower in the highly permeable core compared to that in the low-permeable core Since flue gas primarily consists of nitrogen gas, which plays a crucial role in maintaining pressure during flue gas injection, it is imperative to investigate how variations in flue gas composition affect pressure drop and oil recovery. Shokoya et al 51 conducted experimental investigations on the impact of three distinct flue gas compositions within a slim tube.…”
Section: Effect Of Fracture and Matrix Permeability During Flue Gas I...mentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to a constant TPG, the changes with water saturation in the TPG have a more significant effect on productivity. Mansi et al 8 provided a practical screening tool to manage and predict the efficiency of enhanced gas recovery (EGR) and CO 2 sequestration in shale reservoirs based on the gathered data from across publications of numerical modeling studies and experimental investigations. They found that shallow shale reservoirs with high fracture permeability, total organic content, and CO 2 −CH 4 preferential adsorption capacity are favorable targets for CO 2 -EGR.…”
mentioning
confidence: 99%